Recent and Projected Future Wildfire Trends Across the Ranges of Three Spotted Owl Subspecies Under Climate Change - Wan, Ho Yi; Cushman, Samuel A.; Ganey, Joseph L. (Frontiers in Ecology and Evolution, 2019)
A major task for researchers in the 21st century is to predict how climate-mediated stressors such as wildfires may affect biodiversity under climate change. Previous model predictions typically do not address non-stationarity in climate-fire relationships across time and space. In this study, we applied spatially-explicit non-stationary area burned projection models and high-severity fire probability models to evaluate recent and future trends in area burned, as well as risk of high-severity fire in recent times, across the ranges of three spotted owl subspecies in western United States. Results suggest that the proportion of area burned will increase within the range of all three subspecies under climate change. Additionally, there are inter- and intra-subspecies variations in percent area burned and high-severity fire risk. We recommend more studies to be conducted to understand the interaction and synergistic effects of climate change and wildfire on the spotted owl, especially in regions that are understudied such as Mexico.